PENGARUH PENGGUNAAN MEDIA DIGITAL WORDWALL TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Dita Dwi Lestari; Aries Tika Damayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this research is that in the learning process, teachers have not utilized learning materials optimally. Learning activities still use images found in textbooks, worksheets, and ordinary printed images as aids so that students feel bored in the learning process. The type of research used in this study is quantitative experimental research. Quantitative experimental research is research that aims to test the cause and effect relationship between variables. This research was conducted in class V SDN 3 Kepoh Kota Blora located at Karangtengah 11/7, Kepoh, Jati District, Blora City, Central Java. The results of the study show the results of a research questionnaire on 15 research subjects, obtained from questionnaire data based on 7 statement items. The results of the questionnaire show that as many as 15 students are classified as having very high learning outcomes with a percentage of 100%. Therefore, it can be concluded that the research subjects' learning motivation with the use of digital wordwall media is very high. The use of digital wordwall media can influence students' learning motivation. Based on the results of the hypothesis test calculations, the p-value is 0.000. These results indicate that the p-value <α (0.05), thus H0 is rejected and Ha is accepted. This means there is a significant difference between the two groups. Therefore, it can be concluded that there is a significant difference in the influence of the use of digital media Wordwall on the learning motivation of elementary school students.